ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMEL PADA PT. BANK MEGA INDONESIA PERIODE TAHUN 2003-2013 - Alin, Geby; Mayes, Anthony; ', Rosyetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The role of national banks in developing economies is one of the sectors that are expected to play an active role in supporting the activities of national and regional development, through factor trust and soundness of banks that affect prospectiveinvestors against a bank. This study aimed to examine the bank kesahtan at PT. Mega Bank Indonesia in the period 2003 - 2013 by using CAMEL which consists of 7 ratios are: Capital Adequacy Ratio (CAR), Assets Quality (KAP), Allowance for EarningAssets (PPAP), Net Profit Margin (NPM), Return On assets (ROA), Operating Expenses to Operating Expenses (ROA), Cash Ratio (CR), and a loan to deposit ratio / Financing Deposit Ratio (LDR / FDR). From the analysis it can be concluded that PT. Mega Bank Indonesia from 2003-2013 predicated quite healthy, that as the appropriate standard of health value awarded fairly healthy bank with a credit score 75.Keywords: CAMEL, conventional, syariah